2019
DOI: 10.1515/corrrev-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen effects on mechanical performance of nodular cast iron

Abstract: The KBS-3 method for long-term disposal of spent nuclear fuel is designed with an external self-standing copper shell, which provides the most important barrier against corrosion and escape of radionuclides, and an internal nodular cast iron insert, which provides the load-bearing structure against external loads. The material intended for the load-bearing insert is ferritic nodular cast iron EN 1563 grade EN-GJS-400-15U. In this paper, hydrogen uptake and sensitivity to hydrogen-induced cracking of the cast i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…The as‐supplied state of the material was studied previously and it was found that the studied DCI showed two peaks, one around 500 K and the other one at 700 K. [ 4 ] These peaks correspond with the existing metallurgical hydrogen of about 2 wt ppm in the studied DCI. In tensile loading, a peak appeared at about 400 K and the 500 K peak shifted closer to 560 K with a large increase in its magnitude under electrochemical hydrogen charging.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The as‐supplied state of the material was studied previously and it was found that the studied DCI showed two peaks, one around 500 K and the other one at 700 K. [ 4 ] These peaks correspond with the existing metallurgical hydrogen of about 2 wt ppm in the studied DCI. In tensile loading, a peak appeared at about 400 K and the 500 K peak shifted closer to 560 K with a large increase in its magnitude under electrochemical hydrogen charging.…”
Section: Resultsmentioning
confidence: 95%
“…The magnitude of the 400 K peak also markedly increased and the location shifted towards 450 K in tensile testing with hydrogen charging. [ 4 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations